Molecular characterization and agronomic biofortification of zinc and β-carotene in selected sweet potato germplasm - Rahman, Khandakar Abu Md Mostafizar (2022)
Micronutrient deficiencies coupled with malnutrition affect key development processes including poor physical and mental development in children. Health impacts of micronutrient deficiency are not always acutely visible; it is therefore sometimes termed ‘hidden hunger’. Sweet potato (Ipomoea batatas L., family: Convolvulaceae) is one of the most traditional root crops in many countries including Bangladesh and Malaysia. Screening and molecular characterization using genetic markers for determining the short duration, Zn and β-carotene enriched sweet potato are very effective tools to confirm this species' diversity. In this regard, the present study we investigated the molecular characterization and agronomic bio-fortification of zinc for higher beta carotene in selected sweet potato germplasm and varieties. Three independent experiments were conducted following randomized complete block design (RCBD) to determine molecular characterization and agronomic bio-fortification of zinc for higher β-carotene. In the first experiment, genetic diversity of 20 sweet potato germplasms were evaluated for their morphological and antioxidative properties. The higher individual tuber root weights (about 0.4 kg) were recorded in SP14 (BARI Misti Alu 14), SP15 (BARI Misti Alu 15), SP16 (BARI Misti Alu 16) and SP20 (VitAto) and it ranges from 0.13 kg to 0.4 kg. Result showed significant germplasm variation in β-carotene content among 20 sweet potato germplasms and it ranges from 0.03 to 27.47 mg/100g fresh weight in SP03 (BARI Misti Alu 03) and SP16 (BARI Misti Alu 16), respectively. The PCA analysis showed that, PC1 accounted from 42.2 percent of the overall variability across the collected germplasm. Considering the phenotypic performance and the correlation matrix of the traits, five germplasm such as SP002 (BARI Misti Alu 02), SP014 (BARI Misti Alu 14), SP015 (BARI Misti Alu 15), SP016 (BARI Misti Alu 16) and SP020 (VitAto) found promising for future breeding programs towards development of carotenoid enriched sweet potato germplasm and β-carotene content of those five germplasm were 13.59, 14.833, 12.35, 11.13 and 13.433 mg/100 g fresh weight. In the second experiment, genetic diversity of 20 sweet potato germplasms were accomplished using simple sequence repeats (SSRs) marker. A total of 64 alleles were generated by the 20 primers throughout the 20 germplasm samples, with locus IBS97 having the highest number of alleles (5) whereas locus IbU33 had the fewest alleles (2). The Polymorphism Information Content (PIC) values for the loci IbL46 and IBS97 varied from 0.445 to 0.730. IBS97 has the highest number of effective alleles (3.704), compared to an average of 2.520. The sweet potato germplasm included in this study had a broad genetic base. SP01 (BARI Misti Alu 01) vs. SP09 (BARI Misti Alu 09) and SP12 (BARI Misti Alu 12) vs. SP18 (Gendut) germplasm pairings had the greatest genetic distance (GD=0.965), while SP01 (BARI Misti Alu 01) vs. SP02 (BARI Misti Alu 02) germplasm couples had the least genetic diversity (GD =0.093). Twenty germplasms were classified into two groups in the UPGMA dendrogram, with 16 germplasms classified as group "A" and the remaining four germplasms, SP10 (BARI Misti Alu 10), SP18 (BARI Misti Alu 18), SP19 (Kuala bikam2), and SP20 (VitAto) classified as group "B”. In the third experiment, both soil and foliar application of Zn were evaluated on growth, yield attributes, bio-chemical characteristics and nutrient content in tuber of five germplasm of sweet potato. There were two doses of Zn applied in soil such as 0 and 2.5 kg/ha and four doses of Zn applied as foliar includes 0, 15, 30, and 45 ppm. The growth, yield contributing characters and yield were increased by Zn irrespective of method of application. The nutrient contents and the bio-chemical compounds were also found to be increased by Zn application. Amino acid content in sweet potato were influenced by foliar application of Zn but not with soil application. The Zn content in the tuber were also found to be increased either through soil or foliar application. It was evident that, the effects of Zn application on different studied parameters were more conspicuous as foliar than those of soil application. Therefore, the present study gives the new insights of screening the collected sweet potato germplasm based on their genetic potentiality of tuber yield, β-carotene content, and ability of Zn biofortification. Among the germplasms studied, VitAto can be planted for achieving the highest yield (26.2 t/ha), BARI Misti Alu 15 for higher protein (Isoleucine, Leucine, Lysine, Methionine, Phenylalanine, and Tryptophan), and while BARI Misti Alu 2 and (BARI Misti Alu 14 for higher β-carotene (13.912 and 14.833 mg/100 g fresh weight, respectively).